2015
DOI: 10.3389/fimmu.2015.00313
|View full text |Cite|
|
Sign up to set email alerts
|

Quantity and Quality of Inhaled Dose Predicts Immunopathology in Tuberculosis

Abstract: Experimental animal models of tuberculosis (TB) have convincingly demonstrated that inhaled dose predicts immunopathology and survival. In contrast, the importance of inhaled dose has generally not been appreciated in TB epidemiology, clinical science, or the practice of TB control. Infectiousness of TB patients has traditionally been assessed using microscopy for acid-fast bacilli in the sputum, which should be considered only a risk factor. We have recently demonstrated that cough aerosol cultures from index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 87 publications
3
44
0
1
Order By: Relevance
“…39 Establishing infection or disease: The quantity and characteristics of the inhaled droplet predict clinical outcomes, with early experiments demonstrating that infectious dose predicts risk of progression to disease. 40 In the cough box experiments, the quantity of aerosolised MTB produced by individuals predicted infection in household contacts better than smear grade or time to culture positivity. 32 It has recently been proposed that larger droplets, settling in the upper airway, might result in immune memory and a positive test for infection but little risk of progression to disease.…”
Section: Airborne Mtb Transmissionmentioning
confidence: 99%
“…39 Establishing infection or disease: The quantity and characteristics of the inhaled droplet predict clinical outcomes, with early experiments demonstrating that infectious dose predicts risk of progression to disease. 40 In the cough box experiments, the quantity of aerosolised MTB produced by individuals predicted infection in household contacts better than smear grade or time to culture positivity. 32 It has recently been proposed that larger droplets, settling in the upper airway, might result in immune memory and a positive test for infection but little risk of progression to disease.…”
Section: Airborne Mtb Transmissionmentioning
confidence: 99%
“…We limited the definition of incipient TB to subjects with Mtb-culture positive sputum or gastric aspirate (subjects <5 years) specimen. This definition almost certainly underestimates the number of incipient TB cases in our study but was suggested as providing the most objective and robust evidence of replicating Mtb which is certainly a pre-requisite for progressive disease and transmission (47)(48)(49)(50). We acknowledge though, that the relevance of Mtb-replication and transient excretion in the early phase of Mtb-infection reported in children (51) and which probably also occurs in adults, could be questioned, as successful containment and spontaneous recovery can be expected in an unknown proportion of subjects (13).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, we argue that our Mtb-culture based definition of subclinical TB is the most objective and robust tool for identification of subjects with high-risk for progressive disease and transmission (42)(43)(44)(45). We acknowledge though, that the relevance of Mtb-replication and transient excretion in the early phase of Mtb-infection reported in children (46), that probably also occurs in adults, could be questioned, as successful containment and spontaneous recovery can be expected in an unknown proportion of subjects (14).…”
Section: Discussionmentioning
confidence: 99%